Development Of Learning Tools For Case Method-Based Cake Decoration Courses In Improving Students' Critical Thinking Skills - Ana Rahmi; Fatma Tresno Ingtyas; Nuwairi Hilda; Dina Ampera; Siti Wahidah (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to determine the process and application of cake decorating learning tools in improving students' critical thinking skills. The results of the study indicate that the Inner Case Method-based learning device has met the validity criteria. Based on the results obtained in the field, there is an increase in the percentage of each data in the field from the simulation stage then an increase is made at the trial stage. Based on the data analysis, the learning device developed meets the criteria with a validity value of 3.86 which means it is valid without revision, a practical value of 3.32 which means a high level of practicality, and can increase the average critical thinking ability test score by 74%.